The role of endothelial glycocalyx in sepsis - Hartawan, I Nyoman Budi; Wiryana, Made (Bali Journal of Anesthesiology, 2019)
ABSTRACTThe surface of endothelial cells is filled with various membrane-bound molecules that form the glycocalyx. The endothelial glycocalyx is a surface layer mainly consisted of glycosaminoglycans that include heparan sulfate, chondroitin sulfate, and hyaluronic acid and its core proteins. Previous studies suggest that endothelial surface glycocalyx shedding could play a role in endothelial dysfunction and inflammation. This article will review the endothelial glycocalyx and its role in sepsis.